Infection Prevention and Control Practices During COVID 19 Pandemic and Itscorrelation with Psychosocial Health among Health Care Workers - Yadav, Omprakash Jatashankar; Nirajkumar, Bharadva; Nagar, Shashwat; Ravi, Rejoice P; Jadhav, Rushikesh Madhukar; Jujara, Mohsin A (National Journal of Community Medicine, 2022)
Background: In COIVD 19 pandemic there were reports which have stated that 70% of HCWs are under psychosocial distress [12] that’s why it becomes more important to find out to what extent psychosocial distress has affected the knowledge of ICP and its quality of measures. Objectives: To findan association between the psychosocial condition of health workersand ICP measured followed. Materials and Methods: A study was conducted among the health workers who worked for COVID 19 through a self-reporting questionnaire with a google form from September 2020 to October 2020. Demographical, ICP measure and psychosocial data were collected from 42 HCWswho have worked in COVID 19 for more than 30 days. Analysis was done by PSPP, Epi info, R and excel. Results: ICPM scale (ICP Measure Followed by HCW) which was the dependent variable and independent variables were T & E (Training and Education), SSRS (Social Support Rate Scale), SRAS (Self-Rating Anxiety Scale), SRDS (Self-Rating Depression Scale), GSES (General Self-Efficacy Scale ), SASR (Stanford Acute Stress Reaction), PSQI (Pittsburgh Sleep Quality Index), Age, Duty hours per day, Hours in PPE per day and violence. By SEM (Structural equation model) association was found between the SSRS score effect on ICPM score (β = 0.38, P = 0.000), Hour in PPE score effect on ICPM score (β = 0.21, P = 0.023), violence effect on ICPM score (β = 0.32, P = 0.001) and SRDS score negatively affect on ICPM score (β = - 0.17, P = 0.059) with Adjusted R Square of 0.6 at P=0.000, RMSEA 0.000, SRMR 0.002, GFI 1.00, AGFI 1.00, NFI 1.00, NNFI 1.00, CFI 1.00, ECVI 0.571. Conclusions: A significant association was found between ICP measures followed by HCWs and training education given to them, social support, hours spent in PPE, violence. Even a significant association was seen between violence and sleep quality, the anxiety of HCWs.